Breach of Contract Settlement of Quasi Equity Agreement Between Investor With Indigenous People Soa Nacikit Migodo at Buru Island - Adonia Ivonne Laturette (Universitas Airlangga, 2023)
Indigenous lands belonging to indigenous peoples are regulated by their respective customary laws. The land is seen as something very valuable and must be defended by the indigenous people. Customary land is land belonging to the customary law community unit. Under the system of land ownership according to customary law, indigenous people can gain ownership over a piece of land by clearing forests, inheriting land, receiving land as a gift, exchanging or granting land with or to another, or expiry/verjaring. This research is a sociological legal research, a legal research method that uses empirical facts taken from human behavior, both verbal behavior obtained from interviews and real behavior through direct observation. Empirical research is also used to observe the results of human behavior in the form of physical and archives. In the profit-sharing agreement between PT. Panbers Jaya and the Soa Nacikit indigenous people, PT. Panbers Jaya was in default because it did not carry out its obligations according to the agreement. After deliberation between the parties, the agreed-upon settlement is that PT. Panbers Jaya will give the agreed rights within the new timeframe.